Harnessing Emotional Intelligence for Effective Leadership in the Technology Sector - Dhungana, Madan; Tamang, Suman (Journal of Emerging Management Studies, 2024)
Purpose – This paper focuses on the Nepalese technology sector and aims to investigate the specific dimensions of Emotional Intelligence (EI) that are most critical for leadership effectiveness. It examines the relationship between leadership effectiveness and five independent variables: self-awareness, social skills, cultural intelligence, resilience, and decision-making, aiming to determine their influence on leadership outcomes.Design/methodology/approach – This study employs descriptive and correlational research designs to examine the impact of emotional intelligence factors on leadership effectiveness. Data were gathered using a cross-sectional method from a sample of 279 corporate employees in six IT companies in Nepal. The questionnaire uses a 5-point Likert scale.Findings and conclusion – The study finds that emotional intelligence is a critical factor in effective leadership, as it enables leaders to understand and manage their emotions and those of their team members. The independent variables examined in this research are crucial elements of emotional intelligence, each contributing to various facets of leadership.Implications – The study emphasizes how important emotional intelligence is to team dynamics, leadership, and organizational success. Prioritizing emotional intelligence (EI) training for leaders is critical for organizations because it can greatly improve employee motivation, conflict resolution, and interpersonal relationships. Additionally, a crucial tactic to address team needs and promote a positive workplace culture is the integration of EI assessment into leadership development and recruitment programs.